Optimización del sistema de inyección de agua de un PAD del Campo Rubiales mediante la evaluación del potencial de los pozos y el rediseño de los equipos de bombeo (2019)
In this project, two optimization strategies of the water injection (disposal injection) system of a Rubiales Field PAD were proposed in order to reduce the high energy consumption required in its operation. To accomplish the above, the simulation software PIPESIM was used as the main tool, since this program allowed simulating the behavior of the water injection system of the PAD for its current operating condition, and for the two alternatives proposed. With the developed simulations, the impact that these scenarios generate over energy waste and energy consumption of the process was analyzed. Finally, both alternatives were financially evaluated using the Net Present Value (NPV) indicator.